Risk Ratio of Osteoporosis According to Body Mass Index, Parity, and Caffein Consumption - Elsa Adlina Limbong; Fariani Syahrul (Jurnal Berkala Epidemiologi, 2015)
The number of osteoporosis cases tends to increase in Indonesia. East Java is one of the five provinces with the highest risk of osteoporosis in Indonesia. The study aims to analyze the comparison of osteoporosis risk according to Body Mass Index (BMI), parity, and caffeine consumption. This research is an observational analytic study with a case-control design. Case samples are women with osteoporosis who live in Surabaya and do osteoporosis examinations at Regional Public Hospital of Dr. M. Soewandhie (RSUD Dr. M. Soewandhie) Surabaya in 2013-2014. The control sample was women who were not osteoporosis patients, domiciled in Surabaya, and did an osteoporosis examination at RSUD Dr. Soewandhie Surabaya in 2013-2014. Respondents consisted of 45 cases and 45 controls obtained using the simple random sampling method. Data obtained through primary and secondary data. The independent variables are body mass index, parity, and caffeine consumption. The analysis was performed using an OR calculation on Epi-info with a significance level of 95% CI. The magnitude of risk for each variable is BMI (OR = 2.99; 95% CI = 1.16 <OR <7.74), parity (OR = 2.72; 95% CI = 1.07 <OR <7.01), and caffeine consumption (OR = 2.41; 95% CI = 0.91 <OR <6.42). The conclusion in this study is that women who have a risk for osteoporosis are BMI <18.5 and have parity ≥ 3 times, so it is recommended that women have a normal BMI and limit the number of births to prevent osteoporosis.